A Cross‐Cultural Validation of the Multidimensional Pain Readiness to Change Questionnaire 2 for Japanese Individuals With Chronic Pain. Issue 6 (3rd April 2019) - Adachi, Tomonori; Sunohara, Momoka; Ogawa, Masashi; Enomoto, Kiyoka; Fujita, Yoshitsugu; Mizuno, Yasuyuki; Miki, Kenji; Yukioka, Masao; Maeda, Lynn; Nishiwaki, Yuko; Itoh, Kazuki; Nakanishi, Miho; et al.
Abstract: Objectives: The Multidimensional Pain Readiness to Change Questionnaire 2 (MPRCQ2) is a reliable and valid measure that assesses readiness to adopt a variety of discrete pain self‐management responses. We sought to translate and evaluate psychometric properties of the Japanese version of the MPRCQ2 (MPRCQ2‐J) in individuals with chronic pain. Methods: One hundred seventy‐three individuals with chronic pain were asked to complete the MPRCQ2‐J, as well as measures assessing pain intensity, pain interference, self‐efficacy, and general readiness to adopt a self‐management approach for pain. Forty‐eight of these participants provided additional MPRCQ2‐J data to assess test‐retest reliability. Results: The findings supported a 2‐factor structure of the MPRCQ2‐J when error covariances between the some of the nine primary scales were allowed. Adequate internal consistencies of the MPRCQ2‐J scales (Cronbach's α ranged 0.71 to 0.86), except for the total score (α = 0.68), were observed. However, adequate test‐retest reliabilities (intraclass correlation coefficients ≥ 0.60) were found for only 59% of the MPRCQ2‐J scales. The MPRCQ2‐J evidenced its construct validity via confirmation of the predicted patterns of associations with validity criterion measures and the anticipated effects of participation in an exercise treatment. Discussion: The findings support the internal consistency (except for the total score) and construct validity for MPRCQ2‐J scales. However, potential limitations with respect to test‐retest reliability of some of the scales were also suggested. The MPRCQ2‐J can be used to examine the role that specific readiness domains of pain self‐management responses may play in an adjustment process in Japanese individuals with chronic pain.